2017
DOI: 10.1038/nsmb.3473
|View full text |Cite
|
Sign up to set email alerts
|

U1 snRNP telescripting regulates a size–function-stratified human genome

Abstract: U1 snRNP (U1) functions in splicing introns and telescripting, which suppresses premature cleavage and polyadenylation (PCPA). Using U1 inhibition in human cells, we show that U1 telescripting is selectively required for sustaining long-distance transcription elongation in introns of large genes (median 39 kb). Evidence of widespread PCPA in the same locations in normal tissues reveals that large genes incur natural transcription attrition. Underscoring the importance of U1 telescripting as a gene-size-based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
142
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 42 publications
10
142
0
Order By: Relevance
“…Similarly, the combinatorial effects of U1 inhibition and Exosc3 depletion were observed in the first intron but not in the fourth intron (Figure 2G). Unlike Exosc3 depletion, U1 inhibition led to about 2 fold increase in PAS-linked unique cleavage sites in the 4th intron, consistent with the idea that U1 suppresses the use of nearby PAS sites throughout the gene (Berg et al, 2012; Kaida et al, 2010; Oh et al, 2017). …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, the combinatorial effects of U1 inhibition and Exosc3 depletion were observed in the first intron but not in the fourth intron (Figure 2G). Unlike Exosc3 depletion, U1 inhibition led to about 2 fold increase in PAS-linked unique cleavage sites in the 4th intron, consistent with the idea that U1 suppresses the use of nearby PAS sites throughout the gene (Berg et al, 2012; Kaida et al, 2010; Oh et al, 2017). …”
Section: Resultssupporting
confidence: 79%
“…This transition could be pictured as a checkpoint where transcription is coupled to the necessary elongation factors that probably include the RNA splicing machinery. A recent report demonstrated that suppression of premature cleavage and polyadenylation by U1 snRNP, called U1 telescripting, is selectively required for long-distance transcription elongation in introns of large genes (Oh et al, 2017). Thus, U1 snRNP telescripting may have pleiotropic roles in transcriptional elongation: regulation of the +1 stable nucleosome-associated elongation checkpoint and subsequent prevention of Pol II termination in downstream large introns.…”
Section: Discussionmentioning
confidence: 99%
“…Second, partial defects in complex formation might be expected to result in partial termination defects instead of the very strong effect caused by exclusive H73A expression. Moreover, recent results show that polyadenylation factors, exemplified by CstF64, assemble on inactive intronic PASs, but this is insufficient to cause termination unless cleavage is activated by U1 snRNA inhibition (Oh et al 2017). Finally, the widespread requirement for Xrn2 in efficient termination is most readily explained by PAS cleavage preceding its action.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of U1 snRNP creates a stress on the splicing machinery as well as on other co-transcriptional events dependent upon the availability of U1 snRNP [121]. A diverse set of SMN transcripts is generated upon depletion of U1 snRNP by an ASO that sequesters the 5′ end of endogenous U1 snRNA [49].…”
Section: Alternative Splicing Of Other Smn Exonsmentioning
confidence: 99%